O acesso direto da pessoa humana à corte interamericana de direitos humanos - Vilela, Helena Cristina Aguiar de Paula (2017)
The direct access (jus standi) of human person to international judicial instances represents the consolidation of her status as subject of international law, titulaire of rights and capacity to vindicate them. In this perspective, the current lack of direct access to the Inter-American Court of Human Rights disregards the recognition of human person as subject to international law, to the detriment to the Court’ effectiveness. The objective of present work is to demonstrate the viability of direct access of human person to the IACtHR, as a means of achieving effectiveness. Initially, it was verified that the definition of subject of international law, based on the doctrinaire construction and judicial precedents, attests that the human being is inserted in the rol of these subjects. Afterwards, the comparative analysis between the Inter-American and European systems demonstrated the initial procedural similarity and the current distinction between the two systems, especially with respect to the right of individual petition to their court and their effectiveness. In fact, the direct access of the human person to the IACtHR, which was investigated in its case-law, was devoted special regard in the votes of the Judge Cançado Trindade. According to Cançado Trindade (2002), the frame of reference, the direct access to the IACtHR represents the rescue of the human being as subject of international law and necessary step for the effectiveness of this Court. The methodological approach used was the hypothetical-deductive. In addition, the comparative procedure permeated the study of the inter-American and European systems, and the hermeneutic examined the case-law of the IACtHR about the central theme. The research technique provided the analysis of texts and statistical data from the Inter-American system bodies, as well as the literature review, supported by authors such as Trindade, Carrillo Salcedo, Pastor Ridruejo, Álvarez, Ramos, among others. Through this research, it is concluded that, the political background in Europe that propitiated reform, which included direct access to the ECtHR, differs from the conditions that the IACtHR presents. The Inter-American system organs face financial problems that infer the incapacity to implement measures that imply in the increase of expenses and also deal with the absence of full accession of the ACHR by the OAS membership. Therefore, the implementation of the reform proposal to the ACHR should take into account the peculiarities of the Inter-American system. To that extent, the IACHR should not be extinguished, but rather should be assumed its role of overseeing the cases before the IACtHR, which should be responsible for analyzing individual communications relating to States that have recognized their compulsory jurisdiction.